2016
DOI: 10.3889/oamjms.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Increase in Aortic and Carotid Intimal Medial Thickness in Type 1 Diabetic Patients

Abstract: AIM:To assess aortic and carotid intima-media thickness (aIMT and cIMT) in diabetic patients.PATIENTS AND METHODS:The study included 75 type 1 diabetic patients and 30 age and sex matched healthy volunteer. A blood sample was taken for analysis of HbA1 and lipid profile and the urine sample was taken for analysis of albumin/creatinine ratio. aIMT and cIMT via ultrasound were also done.RESULTS:cIMT & aIMT were significantly higher in diabetics. aIMT was found to be significantly higher than cIMT in diabetic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…aIMT was found to be higher than cIMT in diabetic patients. This result is comparable with previous studies [ 15 ], [ 16 ]. Järvisalo et al, [ 17 ] revealed that young type 1 diabetic patients had an increased incidence of subclinical atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…aIMT was found to be higher than cIMT in diabetic patients. This result is comparable with previous studies [ 15 ], [ 16 ]. Järvisalo et al, [ 17 ] revealed that young type 1 diabetic patients had an increased incidence of subclinical atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…The studies were conducted in the United States, Turkey, Canada, Germany, Egypt, Austria, Poland, Estonia, Finland, Greece, Australia, Norway, Mexico, Sweden, Serbia, and the Netherlands between 2002 and 2017. Twenty studies included cIMT as outcome, 11,12,14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and four included carotid-femoral PWV as outcome. 13,14,36,37 The characteristics of all 23 studies used for the systematic review are summarized in Table 1.…”
Section: Search Results and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…155 In addition, the age-dependent increase of arterial stiffness and arterial wall thickness is accelerated in diabetic patients. [156][157][158] Therefore, anti-hyperglycemic treatment should be considered in the prevention of vascular aging.…”
Section: Interventions For Vascular Aging Pharmacologic Interventions...mentioning
confidence: 99%